The relationship between Chinese college students’ mate preferences and their parents’ education level - Lin, Wuji; Wang, Jie; Liu, Yutong; Li, Zhuoyu; Lin, Jingyuan (Frontiers in Psychology, 2022)
Parents have an influence on the formation of their children’s mate preferences. This research conducted two studies to test the relationship between parents’ education level and the gender role characteristics (masculinity and femininity) of ideal mate for college students, and the moderating role of urban-rural residence on this relationship. In study 1, 1,033 participants (627 females) reported their explicit attitude toward gender role characteristics for an ideal mate via the Chinese Sex Role Inventory-50. In study 2, we recruited 130 participants (66 females) and used an implicit association test to measure their implicit attitude. Regression-based analyses showed that the higher education level of parents was significantly associated with female students’ mate preferences with high-femininity but low-masculinity traits. For male students, the higher education level of parents was associated with their explicit (not implicit) preferences of mates with high-masculinity but low-femininity traits. The significant moderating effect of urban-rural residence was observed in explicit preference, with the different patterns in gender groups. In conclusion, parents with higher educational attainment might bring up children who are more likely to embrace a partner with non-traditional gender roles (e.g., androgynous individuals, feminine men or masculine women).